2018
DOI: 10.1016/j.ajpath.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Function and Dysfunction of Adult Hippocampal Neurogenesis in Regeneration and Disease

Abstract: The hippocampus is the only known brain region where physiological neurogenesis continues into adulthood across mammalian species and in humans. However, disease and injury can change the level of adult hippocampal neurogenesis, which plays an important role in regulating cognitive and emotional abilities. Alterations in hippocampal neurogenesis can mediate treatment of mental illness or affect the brain's capacity for repair and regeneration. In the present review, we evaluate how adult neurogenesis contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
49
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 60 publications
1
49
0
Order By: Relevance
“…However, almost all existing antidepressants are not particularly effective against cognitive dysfunction [18][19][20][21]. In addition to mood dysregulation, the role of HI neurogenesis in cognitive impairment has been widely studied in general [22,23]. Current evidence suggests that inhibition of HI neurogenesis may also be responsible specifically for the cognitive impairment in depressed patients [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all existing antidepressants are not particularly effective against cognitive dysfunction [18][19][20][21]. In addition to mood dysregulation, the role of HI neurogenesis in cognitive impairment has been widely studied in general [22,23]. Current evidence suggests that inhibition of HI neurogenesis may also be responsible specifically for the cognitive impairment in depressed patients [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that high levels of typical BMP signaling were detected in hippocampal niches. In addition, ligands of the BMP family are involved in the regulation of resting adult hippocampal stem cells and in the control of progenitor cell maturation at multiple stages of the neurogenic lineage [16]. Changes in neurogenesis in the subgranular area of the hippocampal dentate gyrus (DG) have been demonstrated in various animal models of AD and in patients with AD.…”
Section: Introductionmentioning
confidence: 99%
“…In the adult hippocampus, neural stem cells (NSCs) give rise to new dentate granule neurons and astrocytes through a sequential process of cell cycle entry and generation of intermediate progenitor cells (Bonaguidi et al, 2011;Bond et al, 2015). New neurons play critical roles in regulating neural plasticity as well as cognitive and affective behaviors, whereas deficits in adult hippocampal neurogenesis have been implicated in age-related brain disorders (Anacker and Hen, 2017;Choi et al, 2018;Peng and Bonaguidi, 2018). While hippocampal neurogenesis persists throughout adulthood, this process is highly compromised during chronological aging.…”
Section: Introductionmentioning
confidence: 99%